CARDIOSPASM - Nagel, Gunther (1949)
Cardiospasm and megaesophagus are well known clinical and pathological entities but the cause remains obscure. Megaesophagus is probably congenital or developmental in origin. The majority of cases of cardiospasm can be successfully treated by forceful dilatation of the narrow area. Some cases of megaesophagus are best treated by a plastic surgical procedure which enlarges the esophageal gastric opening. Additional experience with this method is necessary before it can be correctly evaluated.